KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU STANDAR PEMBIAYAAN - Azizah, Noor (LPPM Universitas Islam 45, 2024)
The principal has a very important role, one of which has competencies that can support his duties, namely personality, managerial, entrepreneurship, supervision, and social. The purpose of this research is to find out the principal's entrepreneurial competence in improving the quality of financing standards at SMPIT Al Mar'atush Shalihah Islamic Boarding School Bekasi City. The method used in this research is qualitative method. The data collection techniques used are interviews, observations and literature studies. This study shows that the entrepreneurial competence of the head of SMPIT Al Mar'atush Sholihah, can be implemented by setting a direct example by involving himself in entrepreneurial activities with all school members with full responsibility. The quality of financing standards has increased very satisfactorily so that schools can meet all school financing, provide assistance to orphans and dhuafa children who attend SMPIT Al Mar'atush Shalihah and add entrepreneurial equipment and equipment. This states that the principal has entrepreneurial competencies that must be possessed by a school principal in entrepreneurial activities, so that the quality of school financing can be fulfilled properly.